Zinc Methionine Improves the Growth Performance of Meat Ducks by Enhancing the Antioxidant Capacity and Intestinal Barrier Function - Chang, Yaqi; Tang, Huangyao; Zhang, Zhenyu; Yang, Ting; Wu, Bing; Zhao, Hua; Liu, Guangmang; Chen, Xiaoling; Tian, Gang; Cai, Jingyi; Wu, Fali; Jia, Gang (Frontiers in Veterinary Science, 2022)
This study was conducted to investigate the effects of zinc methionine (Zn-Met) on the growth performance, antioxidant capacity and intestinal barrier function of meat ducks. Three hundred and sixty 1-day-old male Cherry Valley ducks were randomly divided into 6 groups, and fed diets with 0, 30, 60, 90, 120 or 150 mg/kg Zn for 35 d. The results indicated that dietary supplementation with Zn-Met substantially increased the ADG, and reduced the F/G during 1-35 d (P < 0.05). Dietary Zn-Met markedly increased the activity of SOD, CAT and GSH, and reduced the MDA content in the jejunum (P < 0.05). The mRNA expression levels of critical antioxidant enzymes (SOD, CAT, and Nrf2) were increased by Zn in the jejunum (P < 0.05). Supplementation with 60, 90, 120 and 150 mg/kg of Zn significantly reduced the DAO activity in the serum (P < 0.05). Different levels of Zn can increase the mRNA expression of OCLN and ZO-1 in the jejunum (P < 0.05). As the level of Zn-Met increasing, the content of MUC2, sIgA, IgA and IgG in the jejunum of meat ducks were increased (P < 0.05). The 16S rRNA sequence analysis indicated that 150 mg/kg of Zn had a higher relative abundance of Verrucomicrobia and Akkermansia in cecal digesta (P < 0.05). In conclusion, Zn-Met improved the growth performance of meat ducks by enhancing intestinal antioxidant capacity and intestinal barrier function. This study provides data support for the application of Zn-Met in meat duck breeding.